Creative thinking processes in high school visual arts classes utilizing new media technology - Salvador, Josemarie Rose R.; Koo, Grace S.; Oyzon, Maria Vanessa Lusung; Olegario, Lizamarie C.; Abesamis, Gerson; Muega, Maricris Acido (Quezon City College of Education, University of the Philippines, Diliman, 2023)
Within the literature on creative thinking in the field of education, recent research has attempted to model the cognitive, affective, and contextual factors associated with the creative thinking process. However, little research has been done on factors associated with the creative thinking process in the digitally enhanced surrounding environment of students. Therefore, in this research, descriptive case study was utilized to explore the use of new media technology in High School Visual Arts classes. This study revealed that students; use of new media technology presented three rationales, namely: Function of New Media Technology, Meaning of New Media Technology, and Affects evoked by New Media Technology, Moreover, the study suggested that the use of new media technology influences the creative thinking of high schoolers through some of the stages in the creative thinking process. Most of the students mentioned the different functions of new media technology that helped them when they were constructing the artworks. As a tool for artistic activities, functional new media technology facilitated artistic creative thinking while non-functional new media technology hindered artistic creative thinking. Also, a member of students mentioned ownership, inspiration, finding humor, and acquiring confidence during artistic activities when using new media technology. These meaning and affects evoked by new media technology supported the facilitation of artistic creative thinking of students. The use of new media technology facilitated artistic creative thinking of students who are creative but lack artistic skills. These results demonstrated the benefits of the use of new media technology in the creative thinking of students.
Thesis
Includes bibliographic references
Keywords: Creative thinking -- Study and teaching (Secondary); Arts -- Study and teaching (Secondary); New media art -- Study and teaching (Secondary); Visual arts; Covid 19 Pandemic -- Philippines